The textbook on lung cancer: time for personalized medicine - Office, Editorial (Journal of Thoracic Disease; Vol 7, No 4 (April 28, 2015): Journal of Thoracic Disease, 2015)
We are glad to announce that the book Lung Cancer is officially published by the AME Publishing Company (Figure 1).